The Development of Motor and Pre-literacy Skills by a Physical Education Program in Preschool Children: A Non-randomized Pilot Trial - Battaglia, Giuseppe; Alesi, Marianna; Tabacchi, Garden; Palma, Antonio; Bellafiore, Marianna (Frontiers in Psychology, 2019)
It is known in the literature that fundamental motor skill acquisition is strongly associated with the development of neuromotor, cognitive, social, and emotional aspects in childhood. Unfortunately, in Italy, the physical education teacher is not included in the school’s core personnel, and it is very hard to find a specific physical education program (PEP) that could improve preschool children’s motor and cognitive status. The aim of this study was to investigate whether the quotient of gross motor development (QGMD) and pre-literacy skills concerning visual analysis and spatial orientation abilities changed after 16 weeks of PEP (2 h/week) in preschool children. We conducted a school-based non-randomized pilot trial. It involved 119 preschool children, clustered in a control group [CG, n = 29, body mass index (BMI): 16.90 ± 3.16 Kg/m2] and an intervention group (IG, n = 90, BMI: 16.00 ± 1.75 kg/m2). Participants were assessed for literacy readiness, locomotor and object control skills before and after the experimental period. IG increased the locomotor, object-control skills and QGMD in response to PEP. As concerns the pre-literacy domain, no significant difference was found in visual analysis and spatial orientation skills between IG and CG groups. However, we detected improvements from baseline to post-test in IG children. In conclusion, this study contributes additional evidence suggesting how a PEP could affect not only motor skills, but also cognitive ones. Consistently with the growing research, interventions based on structured ludic-motor activities ensure health benefits for preschool children. Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT01274117.